SnoN in TGF-β Signaling and Cancer Biology - Pot, Isabelle; Bonni, Shirin (Current Molecular Medicine, 2008)
The Transforming Growth Factor (TGF)-β-Smad signaling pathway regulates diverse biological processes essential for normal development and homeostasis. The Smad-interacting transcriptional modulator SnoN and its related homologs have emerged as important modulators of TGF-β signaling and responses. SnoN forms a physical complex with the TGF-β-regulated Smad2/Smad3 and co-Smad4 proteins and either represses or stimulates TGF-β-induced Smad-dependent transcription in a cell- and promoter-specific manner. In addition, the TGF-β-activated Smads recruit several ubiquitin ligases to SnoN and thereby promote the ubiquitination and consequent degradation of SnoN. Additional modifications of SnoN, including sumoylation, may contribute to the regulation of SnoN function and its role in TGF-β signaling. Collectively, these studies suggest that SnoN function is intimately linked to the TGF-β-Smad pathway in cellular signaling. Although the mechanisms by which SnoN modulates signaling in the TGF-β-Smad pathway are beginning to be characterized, the full range of SnoN functions and underlying mechanisms in normal development and disease processes remains to be elucidated.
Keywords: SnoN